(untitled) (Prilozi za orijentalnu filologiju, 2017)
During the classical period of the Ottoman era, the registry of accreditation and transfer of officers by the chancellor’s office in the Imperial Court, in which appointments and dismissals were held, devolved into personnel registry offices and official annals. In our paper, within the registries of the Bosniak ulema in the Ottoman bureaucracy, we have tried to put together the various informations concerning biographical data, the Ottoman bureaucratic mechanism, contemporary educational and cultural establishments in Bosnia and their works.